Analisis Pengaruh Jumlah Industri Kecil, Jumlah Penduduk, Dan Angka Investasi Terhadap Penyerapan Tenaga Kerja Di Kota Surabaya - Raymond Putra Melrin; Parikesit Penangsang (Nirta Learning Centre, 2025)
This study aims to determine the effect of the Number of Small Industries, Population and Investment Rates on Labor Absorption. This study uses a quantitative descriptive research type. To obtain secondary data taken from the Surabaya City Industry and Trade Service and BPS. The data analysis technique used is the Normality test and the coefficient of determination. The hypothesis test used is multiple linear regression in the form of a t-test. This study was conducted in Surabaya City with a sample of small industry research. The data analysis method in this study is multiple linear regression analysis processed with SPSS version 26. From the multiple linear regression model used in this study, the regression equation Y = 53001.657 + 1.327 + 0.429 + 2.269650 was obtained. The results of the study prove that the Number of Small Industries has no significant effect on Labor Absorption, the Number of Population has a significant effect on Labor Absorption, and the Investment Rate has no significant effect on Labor Absorption, the coefficient of determination (R2) in this study is 0.779 or 77.9%. This shows that 77.9% of labor absorption is influenced by the variables of the Number of Small Industries, Population and Investment Figures. While 22.1% is influenced by other variables not included in this study.